Ultimate ownership, risk-taking and firm value: evidence from China. Issue 1 (1st January 2017) - Su, Kun; Li, Liuchuang; Wan, Rui
Abstract: This article investigates the relationship among ultimate ownership, risk-taking and firm value using firm-level data from Chinese companies. The results indicate that dominant ultimate controlling shareholders exacerbate the agency problem. The larger the divergence between ultimate shareholder's control rights and cash flow rights, the stronger motivation is to reduce corporate risk-taking (CRT) to safeguard private benefits. Furthermore, the presence of a dominant ultimate controlling shareholder is harmful to firm value, and the divergence between its control right and cash flow right has a significantly negative effect on firm value. Corporate risk-taking plays a significant mediating effect between ultimate controlling shareholder and firm value. Based on these results based on theory and practice, we propose a number of practical implications for managers.